2021
DOI: 10.1523/jneurosci.2018-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Visual Attention Modulates Glutamate-Glutamine Levels in Vestibular Cortex: Evidence from Magnetic Resonance Spectroscopy

Abstract: Attending to a stimulus enhances the neuronal responses to it, while responses to nonattended stimuli are not enhanced and may even be suppressed. Although the neural mechanisms of response enhancement for attended stimuli have been intensely studied, the neural mechanisms underlying attentional suppression remain largely unknown. It is uncertain whether attention acts to suppress the processing in sensory cortical areas that would otherwise process the nonattended stimulus or the subcortical input to these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…The intervention would focus on the healthy hemisphere the driving recovery, with a clear benefit in the ease of the approach for stroke survivors. Finally, sensory specific attention has been demonstrated to suppress cortical processing of other senses (Frank et al, 2021;Iurilli et al, 2012), suggesting activity gain for the processing of other senses may be possible using prolonged attention isolation. Four participants were excluded from analysis due to data recording errors, leaving 42 participants in total.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention would focus on the healthy hemisphere the driving recovery, with a clear benefit in the ease of the approach for stroke survivors. Finally, sensory specific attention has been demonstrated to suppress cortical processing of other senses (Frank et al, 2021;Iurilli et al, 2012), suggesting activity gain for the processing of other senses may be possible using prolonged attention isolation. Four participants were excluded from analysis due to data recording errors, leaving 42 participants in total.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular-evoked potentials may also offer the possibility to study more precisely the spatiotemporal dynamics of attentional and cognitive effects reported using other neuroimaging techniques. An fMRI study showed that attentional load in a visual tracking task decreased activity in the PIVC ( 218 ), possibly due to a downregulation of excitatory neurotransmitters and maintenance of inhibitory transmitters to reduce PIVC responses to thalamic inputs ( 219 ). Vestibular-evoked potentials may help to refine the timing of such phenomena as well as to study them in several areas simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical deactivation of anterior or posterior subregions of the macaque PIVC however impairs perceptual judgements of head orientation informed by visual cues (Chen et al, 2016), suggesting the PIVC processes visual motion information. In humans, parieto-insular areas including OP2 deactivate in response to visual motion (Kleinschmidt et al, 2002;Laurienti et al, 2002), particularly when it is the focus of attention (Frank et al, 2016a(Frank et al, , 2020(Frank et al, , 2021. Activation is instead seen in the retroinsular cortex (Brandt et al, 1998;Sunaert et al, 1999;Orban et al, 2003;Frank et al, 2014Frank et al, , 2016b.…”
Section: Discussionmentioning
confidence: 99%